Visually Impaired OLder people’s Exercise programme for falls prevenTion (VIOLET): a feasibility study - Adams, Nicola; Skelton, Dawn; Bailey, Cathy; Howel, Denise; Coe, Dorothy; Lampitt, Rosy; Wilkinson, Jennifer; Fouweather, Tony; De Jong, Lex; Gawler, Sheena; Deary, Vincent; Gray, Joanne; et al. (2019)
BACKGROUND:The visually impaired have a higher risk of falling and are likely to avoid activity. OBJECTIVES:To adapt the existing Falls Management Exercise (FaME) programme, which is delivered in the community, for visually impaired older people (VIOP) and to investigate the feasibility of conducting a definitive randomised controlled trial of this adapted intervention. DESIGN:Phase I – consultation with stakeholders to adapt the existing programme. Two focus groups were conducted, each with 10 VIOP across the study sites. Phase II – two-centre randomised pilot trial and economic evaluation of the adapted programme for VIOP versus usual care. Phases III and IV – qualitative interviews with VIOP and Postural Stability Instructors regarding their views and experiences of the research process, undertaking the intervention and its acceptability. INTERVENTION:This was adapted from the group-based FaME programme. A 1-hour exercise programme ran weekly over 12 weeks at the study sites (Newcastle upon Tyne and Glasgow) and was delivered by third-sector organisations. Participants were advised to also exercise at home for 2 hours per week. Those randomised to the usual activities group received no intervention. OUTCOME MEASURES:These were completed at baseline, week 12 and week 24. The primary potential outcome measure used was the Short Form Falls Efficacy Scale – International. Secondary outcome assessment measures were activity avoidance, current activity, balance/falls risk, physical activity, loneliness, anxiety and depression, work and social adjustment, quality of life and economic costs. Participants’ compliance was assessed by reviewing attendance records and self-reported compliance with the home exercises. Instructors’ compliance with the course content (fidelity) was assessed by a researcher attending a sample of exercise sessions. Adverse events were collected in a weekly telephone call for all participants in both the intervention and control arm. FINDINGS:An adapted exercise programme was devised with stakeholders. In the pilot trial, 82 participants drawn from community-living VIOP were screened, 68 met the inclusion criteria and 64 were randomised, with 33 allocated to the intervention and 31 to the usual activities arm. A total of 94% of participants provided data at week 12 and 92% at week 24. Adherence to the study was high. The intervention was found to be both safe and acceptable to participants, with 76% attending nine or more classes. Median time for home exercise was 50 minutes per week. There was little or no evidence that fear of falling, exercise, attitudinal or quality-of-life outcomes differed between trial arms at follow-up. Thematic analysis of the interviews with VIOP participants identified facilitators of and barriers to exercise, including perceived relevance to health, well-being and lifestyle, social interaction, self-perception and practical assistance. Instructors identified issues regarding level of challenge and assistance from a second person. LIMITATIONS:The small sample size and low falls risk of the study sample are study limitations. CONCLUSION:Although adaptation, recruitment and delivery were successful, the findings (particularly from qualitative research with instructors and participants) indicated that VIOP with low to moderate falls risk could be integrated into mainstream programmes with some adaptations. A future definitive trial should consider graduated exercises appropriate to ability and falls risk within mainstream provision. Other outcome measures may additionally be considered. TRIAL REGISTRATION:Current Controlled Trials ISRCTN16949845. FUNDING:This project was funded by the NIHR Public Health Research programme and will be published in full in Public Health Research; Vol. 7, No. 4. See the NIHR Journals Library website for further project information.